Extraction and phytochemical screening from different parts of franggipani (Plumeria alba) - Mohamad Nor, Maryana; Susanti , Deny; Omar, Muhammad Nor (Academic Information Press, 2012)
Plumeria alba (Apocynaceae) has been used in traditional medicine for the treatment of ulcers, herpes and scabies. The plant aerial parts (stem barks, leaves and flowers) were extracted using various solvents of different polarities, i.e.n- hexane, ethyl acetate, dichloromethane and methanol. In addition, the cold extraction using water was performed to obtain water soluble extract. The phytochemical screening of the crude extracts revealed the presence of tannins, saponins, flavonoids, steroids, terpenoids, cardiac glycosides, phytosteroid and reducing sugar.